Le Corbusier, the city, and the modern utopia of dwelling - Rabaça, Armando (Journal of Architecture and Urbanism, 2016)
In Le Corbusier’s urban plans, the conventional public space of the city is gradually dismembered until it coalesces with the natural surroundings, giving rise to the concept of tapis-vert. Its ultimate expression is found in the Athens Charter. By investigating Le Corbusier’s formative years, this article aims to clarify issues of form and meaning involved in this process. The focus on this early period reveals that the territorial scale of the alliance between city and nature is a central theme of Le Corbusier’s concerns with urban planning, preceding the influence of Latin America in the 1930s which is often seen as its underlying momentum. The focus on form and meaning reveals the inextricable links between this alliance and Le Corbusier’s existential idea of unity. The tapis vert of the Athens Charter will thus be seen as a conceptual argument of the holistic world-view of Le Corbusier’s urban visions: the binding element of meaningful architectural forms and natural world ultimately rooted in his attempt to realize the modern utopia of dwelling.